2021
DOI: 10.1111/petr.14020
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, professional fulfillment, and post‐traumatic stress among pediatric solid organ transplant teams

Abstract: Background: Adverse effects of clinician burnout have been studied across multiple specialties; however, there have been no studies examining rates of burnout among pediatric solid organ transplant teams. This study aimed to measure burnout, work exhaustion, professional fulfillment, and post-traumatic stress symptoms among clinicians and administrators practicing in this high-stress field. Methods:This cross-sectional study utilized a 50 item web-based survey that included the Personal Fulfillment Index and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…The questionnaire participants completed was inspired by previous studies conducted by other researchers that investigated the demographic and occupational characteristics of the participants, such as age, gender, marital status, education level, parenting status, history of comorbid physical and psychiatric illnesses, their pursuits such as hobbies, sports and music, years worked in transplant unit, position, professional background, occupation-related attitudes, and environmental support, etc. 1,2,[19][20][21]…”
Section: Participants and Study Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire participants completed was inspired by previous studies conducted by other researchers that investigated the demographic and occupational characteristics of the participants, such as age, gender, marital status, education level, parenting status, history of comorbid physical and psychiatric illnesses, their pursuits such as hobbies, sports and music, years worked in transplant unit, position, professional background, occupation-related attitudes, and environmental support, etc. 1,2,[19][20][21]…”
Section: Participants and Study Protocolmentioning
confidence: 99%
“…In addition to the heavy workload and long working hours, employees have to witness the struggle against death and illness, which does not match the nature of childhood, and therefore, they may be traumatized. A recent study showed that 15% of pediatric transplant workers develop post‐traumatic stress symptoms due to the death of their patients 19 . These individuals sometimes may have to explain to parents who are often worried and despairing for their children, to respond to their demands, and sometimes to cope with verbal or physical attacks 16,20,21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation